FORMS OF NICKEL IN STORAGE TAILINGS OF COPPER-NICKEL ORES - Chanturiya V.A.; Makarov V.N.; Makarov D.V.; Vasil'eva T.N. (My University, 2004)
The tailing dumps of past years may often be regarded as technogenic deposits. Chemically reactive minerals (magnesium and calcium carbonates, serpentine, and some others) can readily interact in the fine-dispersed state with acid salts of Fe, Ni, and Cu salts, resulting in the precipitation of Fe and Cu as hydroxide and basic sulfate, respectively. Tailings are marked not only by sulfide oxidation an the removal of water-soluble sulfates, but also by the interaction of sulfates with the silicate matrix. Although complete equilibrium is not achieved even within 30 yr under polar-region conditions, the major part of the Ni in fine-grained fractions passes into silicate form.